Investigating the needs and barriers for prevention, control, and treatment of HIV/AIDS in transgender population: a systematic review of literature - Heshmatollah Sofimajidpour; Ghobad Moradi; Hojat Dehghanbanadaki; Marzieh Mahboobi; Mobin Azami; Parisa Khodakhah; Mohammad Aziz Rasouli; Yousef Moradi (HIV & AIDS Review. International Journal of HIV-Related Problems)
Introduction The purpose of this systematic review was to identify the health needs related to prevention, control, and treatment of human immunodeficiency virus (HIV)/acquired immunodeficiency syndrome (AIDS) in transgender people from the perspective of transgender individuals and health policy-makers.